THE ROLE OF TRANSPORTATION NETWORK IN THE INTEGRATION OF HAUSA AND YORUBA ETHNIC NATIONALITIES IN FUNTUA TOWN OF KATSINA STATE, NIGERIA - Dangiwa, Abubakar Lawal; Ndawayo, B. A. (FUDMA JOURNAL OF SCIENCES, 2022)
The paper examined the role of transportation network in the integration of Yoruba-Hausa ethnic nationalities in Funtua Town of Katsina State. The study was inspired by agitations being made by some notable Nigerians about the possibilities of disintegration of Nigeria as corporate national entity along the lines of ethnic nationalities. This notion is often propelled by sporadic ethnic and tribal disturbances that occur in the country.  However, the cordial relationship that exists in Funtua town between the Yorubas from southwestern axis of Nigeria and the indigenous Hausas cast doubt to such divisive agitations. The data obtained for this study was principally from primary source, which included discussions, in-depth face-to-face interviews, key informant and physical observational techniques. Reasons for the mixing of the two distinct ethnic groups have been investigated and discussed. The study found out that Yorubas migrated during the pre-colonial, from majorly Ogbomosho, Saki and Lagos areas, and founded Funtua at Ile Amodu and Ile Akile clans. The process continued, where Ile Ogbomoso, Ile Amodu and Ile Akile clan were established during the pre-colonial period, when the creation of rail and road networks facilitated the migration and acculturation processes, as Funtua town was linked with the Yorubaland. While, other factors related to costume and beliefs play vital role in strengthening the mutual bond between the two distinct ethnic groups into indivisible one
Keywords: integration, Hausa, rail, Yoruba, Funtua town, Ile Ogbomoso